Predictive Application Value of Metagenomic Next-Generation Sequencing in the Resistance of Carbapenem-Resistant Enterobacteriaceae - Jiacheng Tian; Chengtan Wang; Pingping Song; Zhiqing You; Xiuqin Jia; Xuan Li; Feng Pang (Canadian Journal of Infectious Diseases and Medical Microbiology)
Conclusion: mNGS demonstrated high sensitivity in predicting the presence of carbapenemase resistance genes in CRE, showing potential in early indication of isolate resistance information, thereby facilitating timely guidance for clinical treatment strategies.